2013
DOI: 10.1519/jsc.0b013e3182891672
|View full text |Cite
|
Sign up to set email alerts
|

Greater Gains in Strength and Power With Intraset Rest Intervals in Hypertrophic Training

Abstract: We sought to determine if hypertrophic training with intraset rest intervals (ISRs) produced greater gains in power compared with traditional rest (TRD) hypertrophic training. Twenty-two men (age 25 ± 5 years, height 179.71 ± 5.04 cm, weight 82.1 ± 10.6 kg, 6.5 ± 4.5 years of training) matched according to baseline characteristics were assigned to 12 weeks of training using TRD or ISR. Body composition, strength (1-repetition maximum [1RM] bench and squat), and power output (60% 1RM bench and squat, and vertic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
49
4
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 21 publications
4
49
4
2
Order By: Relevance
“…Thus, while the beneficial effects of CLU in the acute setting using both Olympic and traditional exercises (squat and bench press) are unequivocal, as evidenced by studies reporting greater force (Hardee et al 2012b), velocity (Hardee et al 2012b;Izquierdo et al 2005), and power (Hardee et al 2012b;Lawton et al 2006), limited investigations have shown beneficial effects on long-term gains following CLU training when compared with TRD. Favorable effects of CLU on muscular power have been reported when participants incorporated CLU in training at or near the optimal load (the load at which the greatest power output is observed) (Kawamori and Haff 2004) for mechanical power output in the respective exercise (Izquierdo et al 2006;Oliver et al 2013;Zarezadeh-Mehrizi et al 2013), while TRD elicited similar power gains (Lawton et al 2004) when training above the optimal load. Interestingly, the recommended intensity for the development of hypertrophy [67-85 % one-repetition maximum (1RM)] is most closely related with the intensities identified for the development of muscular power in trained subjects performing multi-joint exercises (Kawamori and Haff 2004).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, while the beneficial effects of CLU in the acute setting using both Olympic and traditional exercises (squat and bench press) are unequivocal, as evidenced by studies reporting greater force (Hardee et al 2012b), velocity (Hardee et al 2012b;Izquierdo et al 2005), and power (Hardee et al 2012b;Lawton et al 2006), limited investigations have shown beneficial effects on long-term gains following CLU training when compared with TRD. Favorable effects of CLU on muscular power have been reported when participants incorporated CLU in training at or near the optimal load (the load at which the greatest power output is observed) (Kawamori and Haff 2004) for mechanical power output in the respective exercise (Izquierdo et al 2006;Oliver et al 2013;Zarezadeh-Mehrizi et al 2013), while TRD elicited similar power gains (Lawton et al 2004) when training above the optimal load. Interestingly, the recommended intensity for the development of hypertrophy [67-85 % one-repetition maximum (1RM)] is most closely related with the intensities identified for the development of muscular power in trained subjects performing multi-joint exercises (Kawamori and Haff 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the recommended intensity for the development of hypertrophy [67-85 % one-repetition maximum (1RM)] is most closely related with the intensities identified for the development of muscular power in trained subjects performing multi-joint exercises (Kawamori and Haff 2004). However, differing effects of CLU have been reported when utilizing hypertrophic intensities in trained and untrained males (Goto et al 2005;Oliver et al 2013). Oliver et al (2013) recorded greater strength and power following a 12-week resistance training program incorporating hypertrophic intensities with CLU compared with TRD in a group of trained males.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These greater gains in strength occurred, despite no significant differences in hypertrophy or fiber type changes between traditional and cluster trainings. This is suggesting a possible neuromuscular adaptation [19]. The lower body strength and power adaptation in the squat (strength) and jump squat (power) movements compared between a cluster intervention and traditional resistance training resulted that strength significantly increased in both groups.…”
Section: Introductionmentioning
confidence: 89%